Epstein-Barr Virus LMP-1 Natural Sequence Variants Differ in Their Potential To Activate Cellular Signaling Pathways - Fielding, Ceri A. (American Society for Microbiology, 2001)
The latent membrane protein 1 (LMP-1) oncogene of Epstein-Barr virus (EBV) is believed to contribute to the development of many EBV-associated tumors, and there is evidence that sequence variation can affect some functions of LMP-1. Most studies have been restricted to the prototype B95.8 LMP-1 gene and genes isolated from EBV of nasopharyngeal carcinoma (NPC) patients. Here, we analyzed the signaling functions of LMP-1 from a panel of nine EBV isolates, including representatives of four defined groups of European LMP-1 variants (groups A to D [K. Sandvej, J. W. Gratama, M. Munch, X. G. Zhou, R. L. Bolhuis, B. S. Andresen, N. Gregersen, and S. Hamilton-Dutoit, Blood 90:323–330, 1997]) and Chinese NPC-derived LMP-1. Chinese and group D variants activated the transcription factor NF-κB two- to threefold more efficiently than B95.8 LMP-1, while Chinese, group B, and group D variants similarly activated activator protein 1 (AP-1) transcription more efficiently than did B95.8 LMP-1. However, there were no amino acid substitutions in the core binding regions for tumor necrosis factor receptor-associated adapter proteins known to mediate NF-κB and AP-1 activation. In contrast, despite sequence variation in the proposed Janus kinase 3 binding region, STAT activation was remarkably constant among the panel of LMP-1 variants. Analysis of the induction of CD54 (intercellular adhesion molecule 1) protein expression by the LMP-1 variants showed differences that did not correlate with either NF-κB or AP-1. Therefore, while the defined sequence variant groups do correlate with LMP-1 function, the results highlight the fact that the relationship between sequence variation and signaling function is extremely complex. It appears unlikely that one particular amino acid substitution or deletion will define a disease-associated variant of LMP-1.